2008
DOI: 10.2967/jnumed.107.045518
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serotonin and Dopamine Transporter Binding in Psychotropic Medication–Naïve Patients with Generalized Social Anxiety Disorder Shown by123I-β-(4-Iodophenyl)-Tropane SPECT

Abstract: There is circumstantial evidence for the involvement of serotonergic and dopaminergic systems in the pathophysiology of social anxiety disorder. In the present study, using SPECT imaging we examined the 123 I-b-(4-iodophenyl)-tropane binding potential for the serotonin and dopamine transporters in patients with a generalized social anxiety disorder and in age-and sex-matched healthy controls. Methods: Twelve psychotropic medicationnaïve patients with social anxiety disorder, generalized type (5 women and 7 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 33 publications
6
46
2
4
Order By: Relevance
“…Taken together, the hyper-connectivity of cingulate gyrus with the caudate and putamen seeds, as demonstrated in this work, could be indicative of disturbances in striatal function specific to SAD. This is consistent with previous reports from nuclear imaging (van der Wee et al, 2008). Enhanced connectivity in pre-motor regions suggests that SAD patients are in a state of "motor readiness", either due to abnormal input to the striatum (from amygdala or mid-brain dopaminergic neurons) as proposed as a testable model for anxiety disorders by (Marchand, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, the hyper-connectivity of cingulate gyrus with the caudate and putamen seeds, as demonstrated in this work, could be indicative of disturbances in striatal function specific to SAD. This is consistent with previous reports from nuclear imaging (van der Wee et al, 2008). Enhanced connectivity in pre-motor regions suggests that SAD patients are in a state of "motor readiness", either due to abnormal input to the striatum (from amygdala or mid-brain dopaminergic neurons) as proposed as a testable model for anxiety disorders by (Marchand, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Coordinates are reported in the Montreal Neurological Institute standard space. investigating the DA system in SAD have provided only partial support for this hypothesis (van der Wee et al, 2008;Tiihonen et al, 1997;Warwick et al, 2012). Previous studies of striatal D2-R have reported no differences (Schneier et al, 2009), or lower levels in patients (Schneier et al, 2000), as compared to the present results of elevated extrastriatal D2-R availability.…”
Section: Discussioncontrasting
confidence: 45%
“…Investigations comparing SAD patients to control subjects have reported both decreased (Tiihonen et al, 1997), increased (van der Wee et al, 2008) and unchanged (Schneier et al, 2009) dopamine transporter (DAT) availability, as well as reduced (Schneier et al, 2000) or unchanged D2-R availability (Schneier et al, 2009). It is noteworthy that all of these studies have focused on the striatum, whereas blood flow and activation studies have mainly shown extrastriatal regions to be involved in the pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…SAD may be a psychosocial reaction to the stigmatizing PD symptoms such as tremor and bradykinesia, but abnormal function of the striatum has been pointed as one of the key pathophysiological mechanism implicated in SAD [20][21][22][23] and it is also plausible that the profound disruption of the main catecholaminergic and serotonergic pathways that occurs in PD 24 predispose patients to SAD. In our sample, SAD was associated with the intensity of motor symptoms, younger age and with earlier age at disease onset, all of which imply both in higher psychosocial stress and in more severe nigrostriatal dopaminergic denervation 25,26 .…”
Section: Discussionmentioning
confidence: 99%